The Antioxidant Growth and Potency of Yeast Rhodosporidium paludigenum DUCC Y-007 on Different Mediums - Kusdiyantini, Endang; Budiharjo, Anto (JURNAL SAINS DAN MATEMATIKA, 2014)
The antioxidant growth and potency of yeast Rhodosporidium paludigenum DUCC Y-007 have been studied on two treatment mediums. The yeast could grow on two treatment mediums and the dry weight results obtained during the incubation period of 120 hours were 7.17 g/L and 7.33 g/L. The concentration of reducing sugars in stabilized medium were 3.14 g/L and 3.30 g/L at 72-120 hours incubation time respectively. There were differences in pH changes during incubation time which at YPG medium, it tended to increase whereas at semi synthetic medium, the pH tended to decline. Total carotenoid on YPG medium was 50.13 Âµg/g cell and on the semi-synthetic medium was 197.50 Âµg/g cell. Antioxidant activity measured by DPPH reagent showed the results at YPG medium was 50% and at semi-synthetic medium was 61%.